An investigation into the development, principles and practice of environmental interpretation in South Africa: a case study of the National Parks Board - Milne, Ian Bertram (Rhodes University, Faculty of Education, Department of Education, 1996)
This study looks firstly at the historical background to conservation, particularly in the South African National Parks Board, and relates this to developments in interpretation in the National Parks. These are evaluated against international norms as they appear in the current literature. The aim is to establish a platform upon which future developments in interpretation may be built, avoiding the mistakes of the past, while capitalising on the strong points. Current views of what interpretation is, and what it should be, are reviewed. Knowing who the audience is, in terms of cultural background, education, needs and interests, as well as sound planning, clear objectives and ongoing evaluation of interpretive programmes, emerge as essential prerequisites for effective interpretation. Through reviewing the development and current status of interpretation in the National Parks, the study finds that although the view has been expressed by management, both past and present, that interpretation in the national parks is of great importance, the past and current status of interpretation does not reflect that view. Generally, interpretation appears to be regarded as a non-essential service. This report argues that environmental interpretation should be given a higher status in the National Parks Board and that it should form an important part of the conservation strategy and management plan for the national parks. The researcher contends that a greater investment in interpretation could lead to a decrease in the need for further, increased investment in law enforcement in the parks. The researcher is also of the opinion that interpretation aimed at all levels of personnel of the National Parks Board is at least as important as interpretation aimed at visitors.
Keywords: National parks and reserves -- South Africa; Environmental education -- South Africa; National parks and reserves -- Interpretive programs; Conservation of natural resources -- South Africa